2000
DOI: 10.1254/jjp.82.326
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Inhaled Low Molecular Weight Heparin on Airway Allergic Inflammation in Aerosol-Ovalbumin-Sensitized Guinea Pigs

Abstract: Low molecular weigh, heparin (LMWH) possesses multiple nonanticoagulant properties. In the present study, we observed its anti-airway allergic inflammatory effects by bronchoalveolar lavage in guinea pigs. Guinea pigs were sensitized by repeatedly inhaling aerosolized ovalbumin. LMWH (400 u/l, 800 u/l), dexamethasone (1.2 mg/1) or vehicle (normal saline) was inhaled for 7 days. Then the animals were sacrificed under anesthesia and then lavaged with ice-cold Hank's buffer immediately; bronchoalveolar lavage flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
0
3
0
2
Order By: Relevance
“…Setting HS (PGs) as therapeutics Heparin, low molecular weight heparin Cerebral ischemia (38), peritonitis (39,155,172), delayed type hypersensitivity (39), meningitis (173), allergic encephalomyelitis (174), airway (allergic) inflammation (175)(176)(177)(178)(179), hepatic ischemia/reperfusion (180), cutaneous inflammation (178,181), myocarditis (182), renal ischemia/reperfusion (183,184) marrow, via presentation of the stem cell chemokine stromal derived factor-1 and adhesive interaction with Lselectin (48,91,148). Interestingly, bone marrow endothelial cells were shown to express more highly sulfated HS than human umbilical vein endothelial cells, favoring both chemokine and L-selectin binding (149).…”
Section: Compoundsmentioning
confidence: 99%
“…Setting HS (PGs) as therapeutics Heparin, low molecular weight heparin Cerebral ischemia (38), peritonitis (39,155,172), delayed type hypersensitivity (39), meningitis (173), allergic encephalomyelitis (174), airway (allergic) inflammation (175)(176)(177)(178)(179), hepatic ischemia/reperfusion (180), cutaneous inflammation (178,181), myocarditis (182), renal ischemia/reperfusion (183,184) marrow, via presentation of the stem cell chemokine stromal derived factor-1 and adhesive interaction with Lselectin (48,91,148). Interestingly, bone marrow endothelial cells were shown to express more highly sulfated HS than human umbilical vein endothelial cells, favoring both chemokine and L-selectin binding (149).…”
Section: Compoundsmentioning
confidence: 99%
“…This issue has received considerable attention, and resulted in the design and development of varied devices to provide consistent drug delivery to the deep lung tissue [116]. The effective and safe delivery of heparins by this route may be clinically relevant not only for the systemic effect against thrombosis but also for the improvement of localized pharmacotherapy such as in cases of allergy and asthma management [117][118][119].…”
Section: Heparin Containing Dds For Pulmonary Routementioning
confidence: 99%
“…Substantial studies have reported that low molecular weight heparin (LMWH) has various non-anticoagulant properties 12 that play an anti-inflammatory role by reducing the release of IL-6. 13-15 However, the anti-inflammatory effects of LMWH in COVID-19 are currently unknown.…”
Section: Introductionmentioning
confidence: 99%